Examen especial a la cuenta i ngresos por v entas de la Cooperativa de Transporte Alma Lojana de la Ciudad de Loja, periodo 2021 - Mocha Apolo, Jasmin De Los Angeles (2024)
The Work of Curricular Integration denominated: Special examination to the income from sales account of the Cooperative of Transport Alma Lojana, of the City of Loja, period 2021, was oriented to the achievement of the proposed objectives, which include th e assessment of the Internal Control System, the determination of the reasonableness of the balances and the issuance of a report containing comments, conclusions and recommendations with the aim of presenting a contribution to the managers of the Alma Loj ana Transport Cooperative for the appropriate and timely decision making. Various methods were implemented to achieve the objectives according to the audit process. Initially, a preliminary knowledge was carried out through a visit to the cooperative, dur ing which a general diagnosis was obtained. At the planning stage, the internal control of the audited account was evaluated and the necessary tools were prepared for the next phase, the purpose of this phase was to determine the level of risk, establish the audit approach and determine the reasonableness of the balances presented in the financial statements. During the implementation phase, specific programs were implemented and working papers were prepared to support the final report. Finally, the prepar ation and presentation of the final report took place during the reporting phase. This document contains conclusions, comments and conclusions derived from the audit process, providing an overview of the financial situation and internal control in the coop erative. As regards the results obtained, it was found that the organization does not perform bank reconciliations on a regular basis, which may lead to errors due to omission in the recording of transactions, this situation prevents the cooperative from i gnoring the actual balances at the beginning of each month; no detailed record is kept of accounts receivable in order to identify the late payment, the age of balances and the collection management to be carried out; and no supporting documents were provi ded to members as a product of the paid securities. As main conclusion, it was evidenced that the sales revenue of the Transport Cooperative "Alma Lojana" have control deficiencies regarding the implementation and observance of certain aspects of the Manua l of Internal Control for Non Financial Associations and Cooperatives of the Popular and Solidarity Economy.